Reformasi Birokrasi Wali Kota Yogyakarta 2001 – 2011: Telaah Semiotika - Budi Puspo Priyadi; Teuku Afrizal (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The presence of a leader in the Indonesian bureaucratic arena is of significant importance to patrimonial society. As a result, the Indonesian bureaucracy's character is more concerned with the interests of the elite than the people. This was also influenced by the bureaucratic model of colonial and the kingdom. When reformation struck Indonesia in 1998, the character of the Indonesian bureaucracy was no longer suitable with the demands of people in the post-reform era. This study examines the presence of a figure from merchants in the arena of the Indonesian public bureaucracy i.e the Mayor of Yogyakarta. In the midst of lack of leaders serving the people, this figure has drastically changed the context of public service with the idea of "power as a political endowment". This condition is contrary to the culture of the people of Yogyakarta City which are patrimonialism, especially with the existing of Mataram kingdom. This paper applies the bureaucratic reform approach from the top. The results of the study show that  power as a political endowment idea by the mayor of Yogyakarta has changed the style of the bureaucracy which the leader becoming a public servant. Consequently, public services are excellent,  and the local government achieve awards from the central government. In conclusion, changes in the Indonesian bureaucracy can occur with a change approach that was initiated directly by leaders from the top. In fact, strengthening the bureaucratic system is necessary so that bureaucratic changes do not merely depend on the presence of a leader, but it is  rose from an integrated and planned system.